Employee Maintenance Strategy For Millenials Generation In The Era Of Digitalization - Athoillah; Dita Prameswari (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2021)
Background: HR maintenance aims to maintain the stamina of HR in doing work within the company. Human resources that do not get the attention and maintenance of the company will lead to anxiety, decreased enthusiasm and enthusiasm for work, decreased loyalty and achievement. So organizations need to create strategies to retain employees. Purpose: This study aims to provide a reference in organizational practices related to strategies for retaining millennial employees in the digitalization era by improving collaboration skills and good compensation practices from the organization. Methods: This study uses a content analysis method which is based on secondary data that has been collected from books, journals, and the internet on relevant themes and comes from reputable sources. Conclusion: In this study, we prioritize the elements of integration and harmony from each generation which differs in terms of their respective advantages. Because every advantage possessed by HR is a company asset that must be maintained. Thus, a good collaboration and compensation strategy is believed to be able to improve employee performance in the millennial generation (new generation) and the old generation.